Effect of two corticotomy protocols on periodontal tissue and orthodontic movement - Marcelo Lelis ZUPPARDO; Milton SANTAMARIA JR; Camila Lopes FERREIRA; Mariéllen LONGO; Joni Augusto CIRELLI; Mauro Pedrine SANTAMARIA; Maria Aparecida Neves JARDINI (University of São Paulo, 2020)
Abstract Objective To compare two corticotomy surgical protocols in rats to verify whether they alter conventional orthodontic movement. Methodology Sixty Wistar rats were divided into three groups - orthodontic movement (CG), orthodontic movement and corticotomy (G1) and orthodontic movement with corticotomy and decortication (G2) - and euthanized after 7 and 14 days. Tooth movement (mm), bone volume fraction and bone volume ratio to total volume (BV/TV), and bone mineral density (BMD) were evaluated by micro-CT. The total amount of bone was measured in square millimeters and expressed as the percentage of bone area in the histomorphometry. The number of positive TRAP cells and RANK/RANKL/OPG interaction were also investigated. Results Day 14 showed a statistically significant difference in orthodontic tooth movement in CG compared with G1 (7.52 mm; p=0.009) and G2 (7.36 mm; p=0.016). A micro-CT analysis revealed a difference between CG, G1 and G2 regarding BV/TV, with G1 and G2 presenting a lower BV/TV ratio at 14 days (0.77 and 0.73 respectively); we found no statistically significant differences regarding BMD. There was a difference in the total amount of bone in the CG group between 7 and 14 days. At 14 days, CG presented a significantly higher bone percentage than G1 and G2. Regarding TRAP, G2 had more positive cells at 7 and 14 days compared with CG and G1. Conclusion Corticotomy accelerates orthodontic movement. Decortication does not improve corticotomy efficiency.